2011
DOI: 10.1152/ajpheart.00410.2010
|View full text |Cite
|
Sign up to set email alerts
|

Catechin treatment improves cerebrovascular flow-mediated dilation and learning abilities in atherosclerotic mice

Abstract: treatment improves cerebrovascular flow-mediated dilation and learning abilities in atherosclerotic mice. Am J Physiol Heart Circ Physiol 300: H1032-H1043, 2011. First published December 24, 2010; doi:10.1152/ajpheart.00410.2010.-Severe dyslipidemia and the associated oxidative stress could accelerate the age-related decline in cerebrovascular endothelial function and cerebral blood flow (CBF), leading to neuronal loss and impaired learning abilities. We hypothesized that a chronic treatment with the polypheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 45 publications
7
71
1
Order By: Relevance
“…We used 3-and 12-m/o C57Bl/6 male mice (WT, 29±1 g and 46±3 g, respectively, n=20; Charles River Laboratories, St-Constant, QC, Canada) and 3-and 12-m/o atherosclerotic mice (ATX, 25±1 g and 39±2 g, respectively, n=20). ATX mice are knockout for the low density lipoprotein receptor (LDLR) and express the human apolipoprotein B-100 gene (LDLR −/− ; hApoB +/+ [6,44]). Founders of the colony were generous gifts from Dr. H. Hobbs (University of Texas Southwestern, Dallas, TX, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used 3-and 12-m/o C57Bl/6 male mice (WT, 29±1 g and 46±3 g, respectively, n=20; Charles River Laboratories, St-Constant, QC, Canada) and 3-and 12-m/o atherosclerotic mice (ATX, 25±1 g and 39±2 g, respectively, n=20). ATX mice are knockout for the low density lipoprotein receptor (LDLR) and express the human apolipoprotein B-100 gene (LDLR −/− ; hApoB +/+ [6,44]). Founders of the colony were generous gifts from Dr. H. Hobbs (University of Texas Southwestern, Dallas, TX, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The vessels were opened, pinned, and a picture was taken. Plaque area quantification was calculated with Photoshop software and expressed in percentage of total aortic area [6].…”
Section: Plaque Area Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that increases in pressure elicit increases in resistance of cerebral vessels (Cipolla et al, 2002;Davis and Hill, 1999;Faraci et al, 1989;Heistad and Baumbach, 1992;Kontos, 1981;Osol et al, 2002;Wallis et al, 1996). However, vasomotor responses to increases in flow in isolated cerebral vessels varied: dilation (Drouin et al, 2011;Drouin and Thorin, 2009;Gaw and Bevan, 1993), constriction (Bryan et al, 2001a;Madden and Christman, 1999), and biphasic responses Bevan, 1990, 1991;Ngai and Winn, 1995;Shimoda et al, 1996;Shimoda et al, 1998;Thorin-Trescases and Bevan, 1998) were observed. Importantly, no data are available regarding human cerebral vessels preventing the translation of knowledge from vertebrates to humans.…”
Section: Introductionmentioning
confidence: 94%
“…EX mice had free access to a running wheel (Lafayette Instrument, Lafayette, IN, USA) without reward [5] and ran an average of 2.7±0.2 km/day over the 8-month period of exposure. The polyphenol CAT was dissolved in the drinking water to deliver a daily dose of 30 mg/kg previously shown to lower oxidative stress [18,25], prevent endothelial dysfunction and arterial wall remodeling [6,19,24,25], and improve cognition [18]. During that period, all mice were fed a regular diet (RD, 2018; Harlan Teklad Laboratories, Madison, WI, USA).…”
Section: Animalsmentioning
confidence: 99%